Coastal geomorphology and culture in the spatiality of whaling in the Faroe Islands. Issue 1 (6th August 2012) - Fielding, Russell
<x xml:space="preserve">Abstract</x> This paper explores the suggested relationship between the physical structure of beaches in the Faroe Islands and the spatial history and regulation of the grindadráp – the traditional method of whaling practised by the Faroese in which entire pods of whales are driven ashore by collective effort. Using coastal survey methods, this research shows a lack of strong correlation between beach morphology and the practice and regulation of whaling, except in the case of dramatic near‐shore bathymetric features. The gap between these data points can best be filled through cultural‐historical analysis, which informs our understanding of the dynamics behind the spatiality of Faroese whaling and whale conservation efforts.